Corporate Social Responsibility, Enviromental Accounting, Enviromental Management System dan Enviromental Capabilities (Jurnal Ekonomi dan Bisnis Islam, 2023)
This study aims to examine the effect of Corporate Social Responsibility, Environmental Accounting, and Environmental Management Systems on Environmental Capabilities. The measurement of Corporate Social Responsibility refers to use the Global Reporting Initiative (GRI) score which consists of 91 items to see the level of social responsibility disclosure of the company’s environmental capabilities. The population used in this study are companies listed on the Indonesia Stock Exchange and listed in the 2021 PROPER assessment. The PROPER assessment is a company performance appraisal which is held by the Indonesian Ministry of Environment once a year. The data collection method used in this study was purposive sampling, with companies listed on the Indonesia Stock Exchange and listed on PROPER. Data consisting of 55 data were analyzed. Hypothesis analysis uses descriptive analysis method and multiple linear regression. The result in this study indicate that Corporate Social Responsibility have a significant positive effect on Environmental Capabilities. Meanwhile, Environmental Accounting and Environmental Management System does not have a significant effect on Environmental CapabilitiesKeywords: Corporate Social Responsibility, Environmental Accounting, Environmental Management System, Environmental Capabilities